Rapid differential diagnostic methods of meningitis in adults - Nipanal, Akkamahadevi V.; H., Nagappa (International Journal of Advances in Medicine, 2021)
Background: Acute infections of the nervous system are among the most importantproblems in medicine because early recognition, efficient decision making, and rapid institution of therapy can be lifesaving. Objective of the present study was to find out the usefulness of these two tests, CSF-ADA and CSF-CRP for the rapid diagnosis and differentiation of bacterial, tubercular and viral meningitis in adults. Methods: Fifty meningitis patients were selected after fulfilling the following inclusion and exclusion criteria. A prospective clinical evaluation study is undertaken to study the predictive value of CSF CRP and ADA in relation to various types of meningitis. Results: More than half the cases reported were of tubercular meningitis, followed by viral and pyogenic meningitis. The percentages of tubercular, viral and pyogenic were 52%, 32% and 16% respectively. CRP levels were elevated in pyogenic meningitis; the mean CRP level was 25.26±5.56 mg/dl. ADA activity was found to highest in tubercular meningitis, the mean value was 17.67±8.13 IU/L. Conclusions: Study concluded that combine use of CSF CRP and ADA can be used for early differentiation of bacterial, tubercular, and viral meningitis.